Poor reliability of measurement instruments to assess acute responses to load in soccer players irrespective of biological maturity status - Ruf, L.; Drust, B.; Ehmann, P.; Forster, S.; Hecksteden, A.; Meyer, T. (Pediatric Exercise Science, 2022)
Purpose: To assess the short-term reliability of measurement instruments to quantify the acute psychophysiological response to load in adolescent soccer players in relation to biological maturity. Methods: Data were collected from 108 U12 to U17 soccer players on 2 consecutive weeks (pre, n = 32; at, n = 34; and post, n = 42 estimated peak height velocity). Measurements consisted of the Short Recovery and Stress Scale, a countermovement jump, assessment of leg stiffness, and a submaximal run to assess exercise heart rate and heart rate recovery. Test-retest reliability was assessed with the coefficient of variation (CV) and intraclass correlation coefficient (ICC). Results: Items of the Short Recovery and Stress Scale showed poor reliability across maturity groups (CV = 7.0%-53.5%; ICC = .28 to .79). Only few countermovement jump variables (jump height, concentric impulse, and concentric velocity) possessed good reliability. For most variables of the countermovement jump, reliability was better for the post peak height velocity group followed by at-peak height velocity and prepeak height velocity. Very high levels of reliability across maturity groups were observed for exercise heart rate (CV < 1.8%; ICC > .94), while heart rate recovery was more variable (CV < 16.5%; ICC > .48). Conclusion: Results suggest that the majority of investigated variables have poor reliability, questioning their ability to detect small, yet meaningful changes in acute responses to load in adolescent soccer players.